Effectiveness of Certified Teacher Performance - Nunik Yudaningsih; Loso Judijanto; Degdo Suprayitno; Melly Susanti (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
The purpose of this study is to ascertain the efficacy of certified high school teachers' work in Bengkulu City, as well as the elements that promote and hinder their performance at these institutions. This study employs a qualitative methodology. Data collection methods include observation, documentation, and interviews. The principal, a class teacher, a religion teacher, a sports teacher, and two students were the study's subjects. The findings demonstrated that the qualified instructors' performance in the school cannot be deemed effective and still need improvement. Furthermore, this study found that while the inhibiting factors included inadequate infrastructure and facilities for learning and the incapacity of certified teachers to become proficient in technology, the supporting factors included a welcoming learning environment, strong principal support, and certification allowances.